Some factors regulating albumin catabolism and synthesis - Hoffenberg, Raymond (Department of Medicine, 2017)
Hypoalbuminaemia is an essential accompaniment of protein malnutrition. Yet the level of plasma albumin is usually regarded as a relatively crude reflection of a patient's nutritional status, reduction occurring only after prolonged or severe inadequacy of dietary protein. Brock recognized that a marginal degree of hypoalbuminaemia might be evidence of impending or early deficiency, and suggested that minor grades of "protein subnutrition" could conceivably exist with serum albumin levels still within the normal range. The work reported in this thesis developed originally out of an attempt to explore this possibility, and to characterize some of the changes in albumin metabolism that followed mild or early experimental protein deprivation in man and rabbits. Dynamic studies using albumin labelled with radioactive iodine revealed evidence of early adaptational changes, possibly occurring before alteration in the plasma albumin levels. While these studies shed some light on the response of albumin metabolism to experimental depletion, they failed to provide the hoped-for means by which subclinical protein malnutrition could be detected. From this work, however, it was but a short conceptual jump to the general problem of albumin homeostasis, a consideration of which forms the basis of this thesis. The first approach was a study of changes in albumin synthesis and catabolism in rabbits following limitation of dietary protein intake. Adaptive responses were then investigated in animals, provided with normal protein diets, after protein depletion induced by an alternative method - plasmapheresis - and, finally, after intravenous infusion of albumin solutions. Based on these and reported results, a tentative hypothesis has been adduced to account for the body's adaptation to variation in the plasma albumin pool, brought about by experimental manipulation or occurring spontaneously in disease.